KAJIAN GENDER TERHADAP PERATURAN TERKAIT TINDAK PIDANA KEKERAASAN DALAM RUMAH TANGGA - Ni Komang Ratih Kumala Dewi (Jurnal AKSES, 2019)
Women are indeed the most victims of domestic violence, domestic violence is not infrequently men can also be victims, especially now that we see many in some households husbands are afraid of their wives. In the life of the nation and state we are taught to do justice without any difference either in terms of degree, gender and others. The purpose of writing is directed to find out the legal basis for criminal acts of domestic violence as well as the rules of criminal acts of violence in household are examined in a gender perspective. In the discussion, related to the legal basis regulated in Law No. 23 of 2004 and Law No. 31 of 2014 concerning Amendments to Law No. 13 of 2006 concerning Protection of Witnesses and Victims. Domestic Violence Regulations are reviewed in the gender law No. 23 of 2004 concerning the elimination of household problems that occur when faced with the fact that the sound legal provisions embody gender equality and de jure, but their implementation does not bring about gender equality and justice (de facto) because women get more protection than men as victims of domestic violence.